PENGEMBANGAN MEDIA INTERAKTIF BERBASIS KARAKTER PADA MATERI SISTEM PEREDARAN DARAH MANUSIA UNTUK SMA (Jurnal Pelangi : Research of Education and Development, 2014)
Teachers in the learning process less variable in the use of learning strategies more frequently lectured for teachers in presenting the material and rarely use the media in the learning process much less instill character values. The use of media in teaching is expected to increase creativity, interest and motivation to study. The benefits of interactive learning media is expected to motivate students to learn independently, creatively, effectively and efficiently. The media is expected to be used by biology teachers in any school . This type of research is the development of research . Model and procedure development using 4 - D ( four- D - model ) consists of define, design, develop and disseminate. Stage do not disseminate. Further data collection is done with the validation and test media. Media validated by biology professors and lecturers Indonesian and high school biology teacher. Tests performed on high school students of class XI Earth 2 Padang to determine the practicalities of interactive media. The results of the validation are assessed by 3 people validator to interactive media produced show very valid interactive media with validation value 90.69 %. The results were given to the practicalities of 3 biology teacher and a class of students to the interactive media produced shows very practical interactive media with practicality value of 90.55 % and 86.07 %. From the results of the second assessment criteria states that researchers develop useful media in the learning process , both for teachers and for students.